IMPLIKASI KEPUTUSAN LAJNAH BAHTSUL MASAIL NU TERHADAP PENGAMALAN AGAMA NAHDIYIN - Nasution, Zulkarnain (Hukum tata Negara/Siyasah, 2017)
NU purposely did not base its tradition of thought on al-Qur'an and Hadith directly. This keeps him away from textual thinking and single interpretation of the text. His thinking is more adaptive to change, because the constructed interpretation is a reconstruction of the socio-ethical message of Islam through the reinterpretation of the Qur'an and Hadith in the perspective of the school's thought and history itself.Keyword : Lajnah, Bahtsul Masail, Nahdiyin, Peantern